Impact of Climate Change on the Technical Efficiency of Striped Catfish, Pangasianodon hypophthalmus, Farming in the Mekong Delta, Vietnam. Issue 3 (30th November 2017) - Nguyen, Lam A.; Pham, Tung B. V.; Bosma, Roel; Verreth, Johan; Leemans, Rik; De Silva, Sena; Lansink, Alphons O.
Abstract: The technical efficiency of randomly sampled pangasius farms in the Mekong Delta of Vietnam was estimated using data envelopment analysis, and factors affecting technical and scale efficiency were examined with bootstrap truncated regression. The mean technical efficiency score assuming variable returns to scale was 0.84. The technical efficiency of downstream farmers was higher due to lower energy costs and stocking once a year. Most of the up‐ and midstream farms needed to pump water and stocked at least three times in 2 yr. Regression analysis showed a positive effect on technical efficiency of the farmers' education level and having experienced climate change impact through flooding or salinity intrusion in the past. Farms affected by salinity intrusion had a lower scale efficiency as they reduce stocking frequency and rate. In general, reducing fish mortality and the cost of inputs, increasing scale of operation, and being trained, using appropriate methods, in management strategies may improve technical efficiency.